Mathematics Teachers' Views on Online Learning Implementation Barriers - Alcher J. Arpilleda; Milagrosa P. Resullar; Reubenjoy P. Budejas; Ana Lea G. Degorio; Reggienan T. Gulle; Mark Clinton J. Somera; Roderick Sayod; Bernah Rizza May A. Galvez; Myrna D. Ariar; Emelyn S. Digal; Wilje Mae T. Angob; Joe Mark Stephen D. Atis (Pendidikan Matematika STKIP Kusuma Negara, 2023)
Mathematics teachers face challenges when it comes to delivering instruction, particularly on topics that require practical applications. This study aimed to determine the barriers encountered in implementing online learning during the pandemic. A quantitative descriptive research design was employed, utilizing a survey technique, with twelve mathematics teachers from St. Paul University Surigao as participants. The primary instrument used to gather data was an adapted questionnaire from Mailizar et al. (2020). Statistical tools employed in this study included Frequency Count and Percentage Distribution, Mean and Standard Deviation, and Analysis of Variance. Findings revealed that respondents poorly perceived the identified online learning implementation barriers, specifically, the teacher-level and student-level barriers. Consequently, the school provided them with enough support for the online learning implementation during the pandemic. It is also concluded that the teachers' number of years in service affects the perception of the online learning implementation barrier in terms of the teacher level barriers. Based on the results, it is recommended that additional training and support be provided to both teachers and students to create an effective online teaching and learning environment, as the teacher-level and student-level barriers were found to be most prominent.